Young children nutritional status in Samarinda: does exclusive breastfeeding play a role in stunting prevention? - Safika, Erri Larene; Rachmawati, Ayudhia; Pakki, Irfansyah Baharuddin (BKM Public Health and Community Medicine, 2023)
Purpose: This study investigated the relationship between exclusive breastfeeding and stunting incidence in young children aged 0-59 months. Method: This is an observational study with a cross-sectional approach. There were 100 mothers with young children aged 0-59 months as respondents from Palaran, Samarinda. The dependent variable was children's height-for-age nutritional status, as in normal or stunting, and the independent variable was exclusive breastfeeding. Young children's height was collected by checking their Maternal and Child Health (KIA) book. Parity, family income, mother's education, mother's knowledge, and family support information were also collected by interview. Bivariate analysis was measured with the Chi-square test. Results: There is no association between exclusive breastfeeding and stunting (p-value>0.05). We also found no association between stunting and parity, family income, mother's knowledge, and family support (p-value<0.05). However, we found a significant relationship between stunting and mother education. Conclusion: Exclusive breastfeeding is not associated with stunting in Palaran, Samarinda. Further research is needed to determine the factors associated with stunting in Samarinda.